DESIGN THINKING FOR INCREASING BUSINESS PERFORMANCE: UI/UX DEVELOPMENT AND FEATURES INNOVATION IN THE E-PEKEN SURABAYA GOVERNMENT APPLICATION - Memarista, Gesti; Soegiarto, Laventino (Journal of Accounting, Entrepreneurship and Financial Technology (JAEF), 2024)
The Surabaya Government developed the E-Peken to boost the MSME's performance. Unfortunately, negative user ratings show that the E-Peken program falls short of expectations and has several problems. Thus, this researchcreates solutions based on Android mobile applications to build a new User Interface/User Experience (UI/UX) by Design Thinking Method. The study results in eight new and more aesthetically user-friendly innovation features:delivery information, payment methods, reviews and ratings, filters, helpdesk, chat between sellers and buyers, store registration, and product returns. The research used a straightforward User Experience Questionnaire (UEQ-S) to conduct UI/UX development success tests for 20 buyers and sellers of the E-Peken users, such as supportive (Q1) easy (Q2), efficient (Q3), clearness (Q4), exciting (Q5), interesting (Q6), empowerment (Q7), and leading edge (Q8) indicators. The E-Peken’s new appearance is far superior to its previous design by achieving excellent accreditation in terms of usage overall indicators. The exciting indicator (Q5) saw the biggest improvement, increasing by 57.9% (for seller) and 37% (for buyer). It causes sales to increase because the E-Peken is easier to use in business transactions.